IMPLEMENTATION OF THE POLICY ON THE USE OF THE E-BUDDY APPLICATION IN CORRESPONDENCE AT THE TRANSPORTATION SERVICE OF SIDOARJO REGENCY - Andy Adama Iftida Kaharudin Syach; Eni Rustianingsih (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study aims to analyze implementation policy use E-Buddy application in the correspondence process at the Department Transportation Regency Sidoarjo, with focus on effectiveness, constraints, and strategies applied in optimization system said. Method: Using method study qualitative with approach descriptive, data obtained through interview in-depth, observation direct, and study documentation to employees involved in management correspondence. Results: Research results show that implementation E-Buddy application is capable of increase efficiency channel digital disposition and archiving, however Still found constraint like limitations competence technology part employees, facilities devices that have not been evenly, and need update system periodically. Efforts improvement implementation done through internal training, mentoring technical, as well as strengthening regulations use application. Novelty: This finding confirms that success implementation policy digitalization very influenced by readiness source Power human, means supporters, and consistency managerial in its application.